Insulin secretion in health and disease: genomics, proteomics and single vesicle dynamics. (20th March 2006) - Rutter, G.A.; Varadi, A.; Tsuboi, T.; Parton, L.; Ravier, M.
Abstract : Defective insulin secretion from pancreatic islet β-cells is a sine qua non of Type II (non-insulin-dependent) diabetes. Digital imaging analysis of the nanomechanics of individual exocytotic events, achieved using total internal reflection fluorescence microscopy, has allowed us to demonstrate that insulin is released via transient or 'cavicapture' events whereby the vesicle and plasma membranes fuse transiently and reversibly. Such studies reveal that an increase in the number of abortive fusion events contributes to defective insulin secretion in in vitro models of Type II diabetes. Complementary analyses of genome-wide changes in β-cell gene expression, at both the mRNA and protein levels, are now facilitating the identification of key molecular players whose altered expression may contribute to the secretory defects in the diabetic β-cell.